Health-related quality of life and factors affecting it in type-2 diabetic nephropathy patients: a cross sectional observational study - Kumar, Raghuvansh; Krishan, Pawan; Jhajj, Roopkamal (International Journal of Research in Medical Sciences, 2016)
Background: Diabetes is known to worsen the health related quality of life (HRQoL). The aim of the study was to analyze a comprehensive set of potential determinants of HRQoL in a sample of patients suffering from diabetic nephropathy. Method: 60 patients were enrolled and divided into different groups on the basis of stage of diabetic nephropathy. HRQoL was evaluated using generic and disease- specific questionnaires. Generic instrument included SF-36 and diseases-specific instruments used were D-39 (Diabetes-39) and ADS (appraisal diabetes scale). The scores of these questionnaires were analyzed for their association with various demographic factors. Results: It was observed that quality of life deteriorated with the progression of diabetic nephropathy. On the basis of SF-36 score HRQoL was found to be dependent on, age, HbA1c level, presence of positive family history of diabetes and alcohol consumption. On the other hand D-39 scores showed significant association between HRQoL and various demographic factors such as gender, blood pressure, alcoholic consumption and blood sugar levels. According to ADS scores, HRQoL showed association with alcohol consumption and blood sugar levels. Discussion: HRQoL is associated with multiple factors but high linkage is demonstrated by socio-demographic factors and diabetic complications. A patient centred approach should be helpful to prevent deterioration of HRQoL and thus will decrease the burden of diabetes. A regular checkup and early detection of diabetic nephropathy and its management could further delay the decline in quality of life of these patients.